Changes in gut microbiota in Gynura segetum-induced liver injury - Zhang, Menghui; Liu, Lu; Lian, Jianchun; Zhang, Minna; Yang, Xiaozhong; Wang, Honggang (Frontiers in Microbiology, 2025)
IntroductionGynura segetum (GS) has been shown to induce hepatotoxicity. Growing evidence suggests that the response to herbal medicines may be linked to shifts in the gut microbiota. This study aims to investigate the association between gut microbiota and liver injury induced by GS.MethodsThe mice model of liver injury was established by oral gavage of GS decoction for 4 weeks, with or without the broad-spectrum antibiotics (Abx) or fecal microbiota transplantation (FMT). Liver function was assessed through the hematoxylin and eosin (H&E) staining and biochemical indices. The microbiota in the intestinal tract and peritoneal cavity were determined by 16S rRNA gene sequencing. Senecionine, seneciphylline, ferulic acid, beta-sitosterol, vanillic acid, vanillin, isorhamnetin, quercetin, kaempferol, and luteolin were isolated from GS plants, and the effects of these chemical compounds on the intestinal flora were analyzed.Results and discussionCompared to controls, mice treated with the GS decoction exhibited decreased body weight and increased serum levels of total bilirubin, direct bilirubin, alanine aminotransferase, and aspartate aminotransferase, regardless of whether they were given Abx or FMT. The abundance of Akkermansia (phylum Verrucomicrobia) persistently increased in the GS group. In contrast, other bacterial groups showed different trends under Abx or FMT conditions. Additionally, compared with the GS group, the linear discriminant analysis (LDA) score revealed the increase in abundance of Bifidobacterium, Bacteroides, Ruminococcaceae_UCG-007, and Coriobacteriaceae_UCG-002 in the Abx group, and Blautia and Bifidobacterium in the FMT group. 16S sequencing of ascitic fluid detected multiple bacterial phyla. Moreover, the administration of chemical compounds isolated from the GS plant by gavage did not increase the abundance of Akkermansia in the intestine.ConclusionGS increased the relative abundance of the Akkermansia genus in the intestinal tract. None of the above chemical compounds had this effect. This suggests that some components of GS may promote the growth of beneficial bacteria such as Akkermansia, offering new perspectives for drug development.